2018
DOI: 10.25103/jestr.116.22
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanisms in Dual-Phase Steel: Influence of Martensite Volume Fraction and Ferrite Grain Size

Abstract: The influence of Martensite Volume Fraction (MVF) on fracture mechanisms in a Dual Phase steel with two different grain sizes was studied in this work. Ferrite-Martensite microstructure was obtained by an intercritical heat treatment for both groups of grain sizes. The results show a direct relationship between a higher temperature during the intercritical heat treatment and the increase of the MVF. The fine microstructure with higher MVF presents a high tensile strength and a good ductility. Furthermore, in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…8), obtaining a higher maximum stress and yield stress condition for the HT3. The thermal treatments HT1, HT2, and HT4, exhibit the presence of larger microcavities, this is linked to a condition of greater ductility, these results agree with that reported in [25][26][27], while the HT3 evidences a less ductile fracture characteristic linked to greater maximum stress, so that the resulting surfaces present undulations characteristic of a plastic decohesion mechanism, a condition clearly detectable in electronic fractography [28], On the other hand, the materials whose treatments are HT1 and HT4, evidence the formation of precipitates, which favors the formation of larger microcavities, with smaller cavities around them, this is because there are fewer nucleation sites in microcavities, this condition is studied in the references [5,29,30].…”
Section: Mechanical Characterizationsupporting
confidence: 90%
“…8), obtaining a higher maximum stress and yield stress condition for the HT3. The thermal treatments HT1, HT2, and HT4, exhibit the presence of larger microcavities, this is linked to a condition of greater ductility, these results agree with that reported in [25][26][27], while the HT3 evidences a less ductile fracture characteristic linked to greater maximum stress, so that the resulting surfaces present undulations characteristic of a plastic decohesion mechanism, a condition clearly detectable in electronic fractography [28], On the other hand, the materials whose treatments are HT1 and HT4, evidence the formation of precipitates, which favors the formation of larger microcavities, with smaller cavities around them, this is because there are fewer nucleation sites in microcavities, this condition is studied in the references [5,29,30].…”
Section: Mechanical Characterizationsupporting
confidence: 90%
“…[21,22] Pakzaman et al stated that microstructure volume fraction, phase distribution, and morphology limit the deformation process and the stress partitioning. [23] Furthermore, the authors of the current study have previously documented that increasing the amount of martensite in the ferrite matrix increases the dual-phase steel mechanical response under dynamic impact conditions [24] and fatigue. [25] Due to the intercritical heat treatment temperature range used in the dual-phase steel production, the diffusion mechanism is less effective in transporting interstitial carbon atoms, so the resulting martensite produced during the quenching process has lower yield stress and hardness because of the lower and heterogeneous distribution of carbon content.…”
mentioning
confidence: 51%
“…[ 21,22 ] Pakzaman et al stated that microstructure volume fraction, phase distribution, and morphology limit the deformation process and the stress partitioning. [ 23 ] Furthermore, the authors of the current study have previously documented that increasing the amount of martensite in the ferrite matrix increases the dual‐phase steel mechanical response under dynamic impact conditions [ 24 ] and fatigue. [ 25 ]…”
Section: Introductionmentioning
confidence: 85%
“…Another key microstructure feature of the ferriticpearlitic steel was the initial ferritic grain size. There have been many studies on the effects of d f on mechanical properties of ferritic-pearlitic [65][66][67][68][69] and resultant DP steels [70][71][72]. For instance, Karmakar et al [73] reported that grain refinement in DP steels led to enhancements of both strength and ductility.…”
Section: Initial Microstructurementioning
confidence: 99%